JURIDICAL ANALYSIS OF SUPERVISION OF PRISONERS FOR ALL FORMS OF VIOLATION OF THE LAW TO REALIZE PUBLIC ORDER (Research Study at Class IIA Batam State Detention Center) - Ray Leonard Hutabarat, Parley; Washliati, Laily; Nofrial, Ramon (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
In the context of the state, it is regulated in a criminal justice system as a unitary institution that handles legal issues in the country. The Correctional System is an arrangement regarding the direction and limits as well as ways of fostering prisoners based on Pancasila which is carried out in an integrated manner between coaches, fostered, and the community to improve the quality of prisoners so that they are aware of mistakes, improve themselves, and not repeat criminal acts so that they can be accepted again by the community. , can play an active role in development, and can live normally as good and responsible citizens. Correctional Institutions in dealing with every perpetrator of law violations must prioritize the principles of treatment that aim to "restore" the concept of legal order and social order into the thoughts and behavior of lawbreakers. Thus, the hope to be achieved after the offender has finished serving his sentence is to be able to return to normal life in the midst of society based on lawful behavior and social order. For this reason, it is highly expected that the Government and all related institutions can strive to increase the independence, professionalism and accountability of law enforcement so that they are able to carry out their functions and authorities in accordance with statutory regulations in order to support lawbreakers so that they can create public order.